Genetic insights into the risk of hip osteoarthritis on stroke: A single-variable and multivariable Mendelian randomization. - Zhengze Zhang; Yanan Lian; Yuewen He; Hao Liu; Kai Meng; Yong Wang; Wuhua Ma (PLoS ONE)
Background Hip osteoarthritis has been identified as a potential risk factor for stroke, with previous studies have demonstrated an association between hip osteoarthritis and stroke. This study aims to further elucidate the causal relationship between the two, employing Two-Sample and Multivariable Mendelian randomization methods. Methods SNPs, derived from two extensive GWAS, served as instruments in exploring the association between genetically predicted hip osteoarthritis and stroke risk, utilizing two-sample Mendelian randomization. In Multivariable Mendelian randomization, factors such as cigarettes per day, alcoholic drinks per week, hypertension, body mass index, type 2 diabetes, C-reactive protein, rheumatoid arthritis were incorporated to further account for the independent causal effects of multiple correlated exposures. Results Two-sample Mendelian randomization analysis revealed that hip osteoarthritis exerts a potential causal effect on any stroke, any ischemic stroke, and cardioembolic stroke, while it did not influence large artery stroke and small vessel stroke. Multivariable MR analysis indicated that the causal effect of hip osteoarthritis on any ischemic stroke and cardioembolic stroke was no longer evident after adjusting for C-reactive protein, and similarly, the effect on any ischemic stroke was not observed after adjusting for type 2 diabetes. However, the effects on any stroke, any ischemic stroke, and cardioembolic stroke remained significant after adjustments for hypertension, alcoholic drinks per week, cigarettes per day, body mass index, and rheumatoid arthritis. Conclusion The study demonstrated that elevated hip osteoarthritis, as predicted by genetic factors, was potential associated with an increased risk of any stroke, any ischemic stroke, and cardioembolic stroke, but showed no correlation with hypertension, alcoholic drinks per week, cigarettes per day, type 2 diabetes, C-reactive protein, body mass index levels, and rheumatoid arthritis.